2022
DOI: 10.3390/horticulturae8060494
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cold Stress on Leaf Structure, Photosynthesis, and Metabolites in Camellia weiningensis and C. oleifera Seedlings

Abstract: Camellia weiningensis Y. K. Li. sp. nov. (CW) is an endemic oil-tea species in Guizhou province, distributed in the alpine karst area, which exhibits cold resistance and better economic characters than C. oleifera (CO). The mechanism of cold response in CW seedlings has not been studied in depth. Herein, we performed anatomical, physiological, and metabolic analyses to assess the impact of cold stress on leaf structure, photosynthesis, and metabolites in CW and CO seedlings. Anatomical analysis of leaves showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Moreover, apiose/xylose can also be linked to glucose residues of phenolic/phenylpropanoid glycosides in Gesneriaceae in a taxon-specific way [ 58 , 59 ]. In Camellia species, the enhanced UDP-D-apiose content was found to correlate with cold stress resistance [ 60 ]. The importance of the accumulation of phenolics is further supported by the detection/increased accumulation of the 55 kDa hypothetical protein/81E8-like cytochrome P450 monooxygenase in desiccated samples.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, apiose/xylose can also be linked to glucose residues of phenolic/phenylpropanoid glycosides in Gesneriaceae in a taxon-specific way [ 58 , 59 ]. In Camellia species, the enhanced UDP-D-apiose content was found to correlate with cold stress resistance [ 60 ]. The importance of the accumulation of phenolics is further supported by the detection/increased accumulation of the 55 kDa hypothetical protein/81E8-like cytochrome P450 monooxygenase in desiccated samples.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when crop development reaches the anther differentiation stage, CS can lead to production losses of up to 30–50% (Liu et al, 2019; Hassan et al, 2021). Recent data revealed that CS adversely impacts critical crop growth stages in cereals, resulting in carbohydrate accumulation that alters hormone contents (Xu et al, 2022a). Furthermore, CS significantly affects proteins involved in carbohydrate metabolism, protein folding, dilapidation, and stress, and the synthesis of compatible solutes (Raza et al, 2021b; Mehmood et al, 2021; Raza et al, 2021c; He et al, 2023; Seydel et al, 2022).…”
Section: Impact Of Climate Change and Extreme Temperature On Crop Pro...mentioning
confidence: 99%
“…Many studies have revealed significant changes of primary and secondary metabolites under cold stress, mainly including carbohydrates, organic acids, amino acids, and flavonoids. For instance, the contents of sugars ( e.g ., glucose) and several key metabolites associated with sugar metabolism, including UDP‐glucose, UDP‐apiose, and fructose/glucose‐6‐phosphate constantly elevated during cold acclimation but decreased in levels during deacclimation (Shen et al., 2019; Xu, Huang et al., 2022; Yue et al., 2015). Amino acids, mainly including proline, valine, glycine, glutamine, serine, and tryptophan were highly accumulated in cold‐resistant tea cultivars, while the organic acids accumulated in large quantities were mainly those involved in the tricarboxylic acid (TCA) cycle, such as fumaric acid and α ‐ketoglutarate (Wang, Di et al., 2022).…”
Section: Applications Of Metabolomics In Tea Studiesmentioning
confidence: 99%